Measurement of cytoplasmic free Ca2+ concentration in rabbit aorta using the photoprotein, aequorin. Effect of atrial natriuretic peptide on agonist-induced Ca2+ signal generation. - Y Takuwa; H Rasmussen (The Journal of Clinical Investigation, 1987)
Addition of norepinephrine, angiotensin II, or histamine leads to a transient rise in the cytoplasmic Ca2+ concentration ([Ca2+]i), as measured with aequorin, in rabbit aortic strips. Each induces a [Ca2+]i transient which peaks in 2 min and then falls either back to baseline (angiotensin II) or to a plateau (norepinephrine and histamine). The [Ca2+]i transient is due to the mobilization of Ca2+ from a caffeine-sensitive, intracellular pool. An elevation of [K+] to 35 mM leads to a monotonic sustained rise in [Ca2+]i which depends entirely on extracellular Ca2+, but an increase to 100 mM leads to a [Ca2+]i transient from the mobilization of intracellular Ca2+. Atrial natriuretic peptide does not alter basal [Ca2+]i nor inhibit the [Ca2+]i transient induced by either histamine or angiotensin II, but blocks that induced by norepinephrine, and blocks the plateau phase induced by either histamine or norepinephrine. The peptide inhibits the contractile response to all three agonists and to K+.